Avaliação de diferentes pré-tratamentos sobre caule de milho visando sua aplicação na produção de biogás - Venturin, Bruno (2017)
The need for renewable energy sources is evident today since oil-derived fuels are depleting sources. Lignocellulosic biomass is a promising energy source because it has a high content of cellulose, which can be converted to biogas. Currently, biogas production is associated with the treatment of one of the greatest swine problems in Brazil, the management of the high effluent load generated by the confined animal production systems. In this work, different types of pre-treatments of a lignocellulosic raw material, the corn stalk (Zea mays), were investigated using experimental design methodology, as well as the potential of biogas production through co-digestion with swine waste. Pretreatment with H2SO4 showed a significant removal of the hemicellulose fraction using low acid concentrations (0.75%). However, because it also increased the lignin fraction in the biomass, this technique is not suitable for the subsequent production of biogas, since it ends up inhibiting the co-digestion process. On the other hand, pre-treatment with alkaline H2O2 (pH 11.5) achieved an increase in the cellulose fraction of 73.4% and a reduction of 71.6% in lignin content using 12% (v.v-1) of H2O2, 58 °C of orbital agitator temperature, 130.0 rpm stirring and 3.0% of solids content (3 g of dry mass at 100 mL of solution) for 58.0 min. This pretreatment is recommended for biogas production as it provided a 22% increase in the final volume of biogas and a one-third reduction in the digestion time in comparison to the untreated biomass. There was no significant difference between the use of the material containing all particle sizes and the material with only the most abundant particle size (0.890 mm). The ultrasound system with maximum irradiation power of 132 W is not indicated for lignocellulosic pre-treatments as it does not promote changes in the structural composition of the corn stalk. At the end of this study, a promising alternative was obtained in order to make the carbohydrates present in the corn stalk more accessible for the anaerobic digestion and, as a consequence, to increase the biogas production.